(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
This paper considers the issues in advising, supervising and presenting graduate level work in the creative and performing arts in general, and music performance in particular. It outlines the qualities needed in the mentoring team in the monitoring of folio presentations and their place in the graduate school spectrum. Though some of the examples are in the context of a specific discipline in a particular institution, readers will be able to relate to the problems and to translate the proposed solutions to a more general context.